Decline in the number of patients with meningitis in German hospitals during the COVID-19 pandemic: original communication - Völk, Stefanie; Pfirrmann, Markus; Koedel, Uwe; Pfister, Hans-Walter; Lang, Thomas; Scheibe, Franziska; Salih, Farid; Herzig-Nichtweiss, Julia; Zimmermann, Julian; Alonso, Angelika; Wittstock, Matthias; Totzeck, Andreas; et al. (Journal of neurology, 2022)
In 2020, a wide range of hygiene measures was implemented to mitigate infections caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In consequence, pulmonary infections due to other respiratory pathogens also decreased. Here, we evaluated the number of bacterial and viral meningitis and encephalitis cases during the coronavirus disease 2019 (COVID-19) pandemic.
Gesehen am 02.01.2024